2009
DOI: 10.1007/s10730-009-9114-9
|View full text |Cite
|
Sign up to set email alerts
|

Avian Flu Pandemic – Flight of the Healthcare Worker?

Abstract: Our research demonstrated that the healthcare workers a tour institution voiced an earnest willingness to work in the event of an avian flu pandemic, if provided with the necessary input, protections and tools, and education. The use of an electronic methodology for dissemination of surveys allowed the low-cost solicitation of information from a vast proportion of the workforce with ease, providing the institutional ethics committee with the empirical data needed to articulate more meaningful,thoughtful, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…Twenty-two studies reported the ethical clearance of their study. [3][4][5][6]13,15,20,[22][23][24][25][26][27]29,[31][32][33][35][36][37][39][40] Nurses in the ''post-SARS'' group were more willing to provide care for patients with SARS and agreed more with the general SARS control measures than those in the ''during-SARS'' group . The nurses' levels of agreement with general SARS infection control measures and the need for quarantine after providing care for infected patients were significant predictors of nurses' commitment to their professional obligation. 2004 Gullion 14 20.2% of respondents were not at all willing to care for a patient infected with a communicable respiratory infection such as SARS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-two studies reported the ethical clearance of their study. [3][4][5][6]13,15,20,[22][23][24][25][26][27]29,[31][32][33][35][36][37][39][40] Nurses in the ''post-SARS'' group were more willing to provide care for patients with SARS and agreed more with the general SARS control measures than those in the ''during-SARS'' group . The nurses' levels of agreement with general SARS infection control measures and the need for quarantine after providing care for infected patients were significant predictors of nurses' commitment to their professional obligation. 2004 Gullion 14 20.2% of respondents were not at all willing to care for a patient infected with a communicable respiratory infection such as SARS.…”
Section: Resultsmentioning
confidence: 99%
“…Respondents were more likely to respond to other disasters than an influenza pandemic. 2009 Shabanowitz 31 .60% disagreed that it was ethical to abandon the workplace during a pandemic. 65% of respondents wanted autonomy in deciding whether or not to work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency personnel often described difficulty in finding a balance between their need to be safe and their duty to care, owing to conflicting thoughts about job responsibilities and possible injury or death. 56 Organizational Role and Climate Confidence in the employer's capacity to respond appropriately to employee concerns regarding safety significantly increased employee willingness to respond:y ''If the workforce is not informed of the realistic risk and associated plans to be enacted to minimize exposure, they may not report to work.'' * However, a belief that caring for patients is a moral imperative emerged as the most persuasive factor among physicians and emergency department employees when asked why they intended to respond during a PHE.…”
Section: Nature Of the Phementioning
confidence: 99%
“…Irvin et al [22] examined the willingness of hospital personnel in a Midwestern US medical center to report to work in an avian influenza and factors influencing their decisions. Martinese et al [23] in Australia examined how an avian or pandemic influenza threat would affect hospital staff members' absenteeism while Shabanowitz et al [24] researched willingness of providers at a US medical center. Tzeng and Yin [25] in Taiwan illustrated factors that contributed to nurses' fear about an avian influenza and willingness to care for infected patients.…”
Section: Geographic Locationmentioning
confidence: 99%